2010
DOI: 10.1074/jbc.m109.063388
|View full text |Cite
|
Sign up to set email alerts
|

Apical Surface Expression of Aspartic Protease Plasmepsin 4, a Potential Transmission-blocking Target of the Plasmodium Ookinete

Abstract: To invade its definitive host, the mosquito, the malaria parasite must cross the midgut peritrophic matrix that is composed of chitin cross-linked by chitin-binding proteins and then develop into an oocyst on the midgut basal lamina. Previous evidence indicates that Plasmodium ookinete-secreted chitinase is important in midgut invasion. The mechanistic role of other ookinete-secreted enzymes in midgut invasion has not been previously examined. De novo mass spectrometry sequencing of a protein obtained by benza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…For example, it has been shown that not only surface proteins, such as P25 and P28 family proteins, but also ookinete-secreted proteins may synergize as transmissionblocking vaccine targets. 10,12 To this end, new methods to study the ultrastructure of Plasmodium ookinetes may provide new insights into how to interfere with the biology of malaria parasites to the goal of malaria control. 13 Here, we show new transmission electron microscope morphologies of developing and mature ookinete stages of P. gallinaceum.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that not only surface proteins, such as P25 and P28 family proteins, but also ookinete-secreted proteins may synergize as transmissionblocking vaccine targets. 10,12 To this end, new methods to study the ultrastructure of Plasmodium ookinetes may provide new insights into how to interfere with the biology of malaria parasites to the goal of malaria control. 13 Here, we show new transmission electron microscope morphologies of developing and mature ookinete stages of P. gallinaceum.…”
Section: Introductionmentioning
confidence: 99%
“…PMIV, which was previously only demonstrated to function in the food vacuole of asexual stages, was recently localized to the micronemes and at the apical surface of ookinetes. A second role for PMIV is suspected in mosquito midgut invasion and/or development of oocysts from ookinetes (Li et al, 2010). Most recently, PfPMV has been localized to the endoplasmic reticulum (ER) and was demonstrated to be essential for parasite viability and hence represents a new target for therapeutic intervention against malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the first-line ART containing the PIs LPV/r had the strongest impact on oocyst intensity in vivo (Figures 3E,G). Although, to the best of our knowledge, the effect of ARVs on ookinetes has not been previously reported, it is known that PMs IV, VII, and X (Li et al, 2010(Li et al, , 2016 are expressed by this parasite stage, thus providing a possible explanation for the effect of PIs on the transformation of ookinetes into oocysts. Moreover, PM VI, whose role is yet undefined, seems crucial for the early oocyst stages of sporogonic development (Li et al, 2016).…”
Section: Discussionmentioning
confidence: 86%